Effects of the abiotic factors and physical parameters change to the magnesium (Mg) and iron (Fe) concentration in the abandon mamut copper mine Ranau, Sabah - Julian, Nelly (2020)
Magnesium (Mg) and iron (Fe) were play an important role as essential element for the crop of farmer around the abandon Mamut Copper Mine Ranau Sabah. However, the occurrence of rapid change of abiotic factor and physical parameter could affect the magnesium (Mg) and iron (Fe) concentration in abandon Mamut Copper Mine to decrease or increase and this can cause the deficiencies in crop yield. This study was conducted to determine either abiotic factor or physical parameter can affect the magnesium (Mg) and iron (Fe) in abandon Mamut Copper Mine as a main source of water for the farmer’s crop. Firstly, pH and dissolved oxygen were determined using HI98194 pH/EC/DO Multiparameter (HANNA). After that, five replicates of water samples were collected in each three different station per sampling. The prepared sample were run with the Atomic Absorption Spectrophotometer, AAS (Agilent Technologies 200 Series AA) to determine and identify the concentration of Mg and Fe. The range of magnesium (Mg) concentration is 73.38 ± 2.27 mg/L – 118. 22 ± 0.53 mg/L. While for the iron (Fe), the range is 11.85 ± 0.3 mg/L – 13. 37 ± 0.145 mg/L. The range of pH is 3.06 ± 0.09 – 3.07 ± 0.09. While, for dissolved oxygen, the range is 6.84 ± 0.096 – 6.86 ± 0.098. From the finding, there were variation of the abiotic factor from July to October of year 2019 that obtained from the Sabah Meteorological Department. This show that abiotic factor can be the reason that can derive the magnesium (Mg) and iron (Fe) concentration in abandon Mamut Copper Mine to increase or decrease. Other than that, the result indicates that only temperature and humidity of abiotic factor that have significant correlation with magnesium (Mg) concentration.